Hypofractionated and hyper-hypofractionated radiation therapy in postoperative breast cancer treatment - Fang,Marcel (2020)
SUMMARY INTRODUCTION: Radiation therapy is widely used as adjuvant treatment in breast cancer patients. In the last decades, several studies have been designed to evaluate the safety and efficacy of hypofractionated breast radiation therapy. More recently, even shorter regimens with doses above 4 Gy (hyper-hypofractionation) have also been proposed. This study aims to present a narrative review of the various hypofractionation protocols used to treat breast cancer patients with a focus on clinical application. RESULTS: Long-term results from several phase III randomized controlled trials demonstrated the safety and efficacy of hypofractionated breast radiation therapy using 15 or 16 fractions for early and locally advanced disease. The results of the initial clinical trials of hyper-hypofractionation are also encouraging and it is believed that these regimens may become routine in the indication of adjuvant radiation therapy treatment after the ongoing studies on this subject have matured. CONCLUSIONS: The idea that normal tissues could present high toxicity at doses above 2 Gy was opposed by clinical trials that demonstrated that moderate hypofractionation had similar results regarding oncological and cosmetic outcomes compared to conventional fractionation. Cosmetic and toxicity results from hyper-fractionation studies are in principle favorable. However, the long-term oncological results of studies that used hyper-hypofractionation for the treatment of breast cancer patients are still awaited.